FILOSOFIS SAMPRADAYA DALAM KEHIDUPAN SOSIAL MASYARAKAT HINDU DI BALI (Studi Kasus di Desa Sidatapa, Kabupaten Buleleng) - I Wayan Gata (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Village Sidatapa Banjar District Buleleng district is very thick with tradition and culturaltraditions. The village is quite protekted with customs, religious ceremonies from various outsideinfluences. Lately it is in and growing sampradaya Hare Krishna and sampradaya Sai Baba inthe village Sidatapa. Three pertenyaan research that emerged from this phenomenon is How theidentity of sampos sampa village in sidatapa village? How about Sampadaya ritual in a societythat is strong in custom and culture? What is the philosophical meaning of the presence ofsampradaya in the village of Sidatapa? This research uses Phenomenological theory, Religiusitastheory and Value theory. Data collection techniques are observation techniques, interviews,document studies, data analysis techniques, qualitative descriptive. Result: (a) The male devoteeswear white or yellow-orange robe, the ladies wearing colorful sari, dancing and singing to theaccompaniment of traditional music India. (b) Sampradaya Sai Baba is guided by AD & ART.(2) Form of Yajna ceremony sampradaya Hare Krishna and Sai Baba namely: (a) HajamaKrishna Yajna ceremony that is by performing Bhajan ceremony every Thursday and also everydayby offering fruits, flowers and water and cakes. (b) The form of the Sai Baba yajna samrpadayaceremony is the Bhajan system. (3) There is a philosopher's similarity between the ritualsampradaya and Hindu ritual philosophy in Sidatapa, which are both depart from the fiveuniversal pillars of Satya, Santhi, Dharma, Prema and Ahimsa. The five teachings of thisphilosophy are then manifested into different forms and ways of offering by the adherents of thefaith adapted to the conditions of the religious environment.